Cardiac device-related endocarditis: Epidemiology, pathogenesis, diagnosis and treatment – a review - Edelstein, Shimon (Pulsus Group Inc, 2009)
Cardiac device-related endocarditis (CDE) is a phenomenon for which incidence is on the rise; it presents difficult management problems to the clinician. On one hand, there is the patient who needs the implanted device, and the potential morbidity and mortality associated with its removal. On the other hand, there is the problem of a persistent infection – usually acquired during insertion of an electrical device – that is resistant to many antibiotics, has a high recurrence rate, and necessitates an extensive operation to remove the device if removal is delayed. Most studies recommend device and metal lead replacement if CDE occurs. The aim of the present review is to raise awareness of CDE among clinicians, and to provide an appropriate approach to its management.